PENGARUH HARGA DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE VIVO DI KUTA UTARA - Hesti Nurfitriani; Ni Made Hartini (Journal Research of Management, 2020)
This study aims to analyze the effect of partial price and brand image on purchasing decisions (Y) on Vivo mobile phones in Kuta Utara. Price is an activity to talk about satisfaction and dissatisfaction with others. In order to achieve company goals, a good brand image is needed so that it can be stored in the minds of consumers to improve purchasing decisions. In this study, it was explained about the positive influence of price and brand image on purchasing decisions partially. Sampling is done by using a purposive sampling technique that is sampling with certain considerations, where the number of samples used in this study were 70 respondents. In this study carried out statistical analysis assisted through SPSS computer program (Statistical for Social Science) Rel.16. From the results of the analysis using multiple regression analysis techniques with the formula Y = a + b1x1 + b2x2 namely price (X1) has a positive and significant influence on purchasing decisions (Y) with a regression coefficient b1x1 of 0.267 and confirmed by the results of t test where tcount = 2.507 > t table (0.05: 109) = 1.659 and sig.t = 0.014 (p <0.05). Brand Image (X2) partially has a positive and significant influence and is confirmed by the results of the t test where it is obtained tcount = 7.407> t table (0.05: 109) = 1.659 and sig.t 0,000 (p <0.05). Based on the description above, it can be concluded that there is a positive and significant influence between price (X1) and brand image (X2) on the purchasing decision (Y) of Mobile Vivo in Kuta Utara.